Flexible all-solution-processed all-plastic multijunction solar cells for powering electronic devices. Issue 5 (28th June 2016) - Tong, Jinhui; Xiong, Sixing; Zhou, Yifeng; Mao, Lin; Min, Xue; Li, Zaifang; Jiang, Fangyuan; Meng, Wei; Qin, Fei; Liu, Tiefeng; Ge, Ru; Fuentes-Hernandez, Canek; et al.
Abstract : Flexible all-plastic multijunction solar cells with high photovoltage have been demonstrated via optimization of the charge-recombination layer and shown to power portable electronics. Abstract : A low-cost, light-weight and flexible power supply is highly desirable for portable electronic devices. All-plastic solar cells in which all the layers are fabricated sequentially from organic synthetic inks could meet these requirements. Here, we report that fully solution-processed all-plastic multijunction solar cells can be easily fabricated layer by layer without the need for sophisticated patterning. The key for the high-yield fully solution-processed multijunction cells is the control and tuning of the conductivity of the charge-recombination layer of PEDOT:PSS/PEI. The all-plastic multijunction solar cells achieve a PCE of 6.1 ± 0.4% and a high open-circuit voltage of 5.37 V. These all-plastic multijunction solar cells are successfully used to drive liquid-crystal displays, full-color light-emitting diodes and for water splitting under different light illumination conditions.